Diseño de la intervención para la estructura de pavimento flexible en secciones representativas de la red vial cantonal de Curridabat - Umaña-Barrios, Andrés Martín (Instituto Tecnológico de Costa Rica, 2015)
The project aims to recommend the type of design to intervene Curridabat major roads with flexible pavement structure through visual classifications and techniques such as the methodology quality notes Q. Therefore it began by a visual pathways auscultation, generating the classification by the PCI (Pavement Condition Index) and recommending intervention rate as the value obtained. A asphalt laboratory was hired to demarche the deflectometry, TPD and calculation of IRI testing, as the results are classified according to their actual condition in order to propose methods of intervention. For calle Mercedes, being the only route of entry to Tirrases district is one of the busiest so an overlay intervention was designed as short-term, through the method of back calculation modulus. They thickness in order to withstand the loads required in a projection 10 years were proposed.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: PCI; Retrocálculo; Módulos; Deflectometría; Auscultación visual; Carreteras